Application of inspection robot in internet data center intelligent operation and maintenance - Xiaosong LIU; Ting HUANG (Dianxin kexue)
The operation and maintenance of the internet data center (IDC) is critical and arduous.Operators urgently need to consider how to introduce inspection robots to improve the level of intelligent operation and maintenance.The development status and technology maturity of the inspection robot industry were introduced and the overall structure of the inspection robot data acquisition system was proposed.Combining with the actual network demand of data center inspection robots,technical breakthroughs in intelligent operation and maintenance of data centers and mining and application of collected data were discussed in depth.